“Mitochondrial Toolbox” – A Review of Online Resources to Explore Mitochondrial Genomics - Cappa, Ruaidhri; de Campos, Cassio; Maxwell, Alexander P.; McKnight, Amy J. (Frontiers in Genetics, 2020)
Mitochondria play a significant role in many biological systems. There is emerging evidence that differences in the mitochondrial genome may contribute to multiple common diseases, leading to an increasing number of studies exploring mitochondrial genomics. There is often a large amount of complex data generated (for example via next generation sequencing), which requires optimised bioinformatics tools to efficiently and effectively generate robust outcomes from these large datasets. Twenty-four online resources dedicated to mitochondrial genomics were reviewed. This ‘mitochondrial toolbox’ summary resource will enable researchers to rapidly identify the resource(s) most suitable for their needs. These resources fulfil a variety of functions, with some being highly specialised. No single tool will provide all users with the resources they require; therefore, the most suitable tool will vary between users depending on the nature of the work they aim to carry out. Genetics resources are well established for phylogeny and DNA sequence changes, but further epigenetic and gene expression resources need to be developed for mitochondrial genomics.